ANALISIS PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR PERTAMBANGAN DI SUB SEKTOR MINYAK DAN GAS BUMI DI BEI - Makmur, Mariam; Salida, Amrizal; Taufiq, Muhammad (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2023)
This study intends to ascertain if the working capital and accounts receivable turnover affect the manufacturing enterprises' profitability in the mining sector, a subsector of the oil and gas industry, partially or concurrently in 2018-2022 BEI. Purposive sampling was used to get this data from secondary sources, including the Indonesia Stock Exchange (BEI) website and other pertinent links. Ten companies are populating that are listed on the Stock Exchange. In comparison, a sample of 6 companies listed there has had their traditional presumptions, analytical techniques, and hypotheses examined through data analysis methodology utilizing regression methods. Because the test findings were negative and insignificant, the results indicated that the idea was rejected. This suggests no negative impact on profitability (ROA) from the working capital turnover.